Glycoprotein gene sequence variation in rhesus monkey rhadinovirus - Shin, Young C. (2010)
Gene sequences for seven glycoproteins from 20 independent isolates of rhesus monkey rhadinovirus (RRV) and of the corresponding seven glycoprotein genes from nine strains of the Kaposi's sarcoma-associated herpesvirus (KSHV) were obtained and analyzed. Phylogenetic analysis revealed two discrete groupings of RRV gH sequences, two discrete groupings of RRV gL sequences and two discrete groupings of RRV gB sequences. We called these phylogenetic groupings gHa, gHb, gLa, gLb, gBa and gBb. gHa was always paired with gLa and gHb was always paired with gLb for any individual RRV isolate. Since gH and gL are known to be interacting partners, these results suggest the need of matching sequence types for function of these cooperating proteins. gB phylogenetic grouping was not associated with gH/gL phylogenetic grouping. Our results demonstrate two distinct, distantly-related phylogenetic groupings of gH and gL of RRV despite a remarkable degree of sequence conservation within each individual phylogenetic group. © 2010 Elsevier Inc.